2011
DOI: 10.1038/ncomms1390
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of 150-cavity formation in influenza neuraminidase

Abstract: The recently discovered 150-cavity in the active site of group-1 influenza A neuraminidase (NA) proteins provides a target for rational structure-based drug development to counter the increasing frequency of antiviral resistance in influenza. Surprisingly, the 2009 H1N1 pandemic virus (09N1) neuramidase was crystalized without the 150-cavity characteristic of group-1 NAs. Here we demonstrate, through a total sum of 1.6 μs of biophysical simulations, that 09N1 NA exists in solution preferentially with an open 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(142 citation statements)
references
References 29 publications
(44 reference statements)
10
127
2
Order By: Relevance
“…Numerous studies have confirmed that the 150-loop is one of the most flexible parts of the influenza NA structure (28)(29)(30), and there are striking structural differences among variant influenza NA subtypes at this site (17,18,20). No 150-cavity in N10 could be identified compared with the uncomplexed typical group 1 VN04N1 (NA from Vietnam 2004 H5N1; PDB ID code 2HTY) and typical group 2 N2 structures (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Numerous studies have confirmed that the 150-loop is one of the most flexible parts of the influenza NA structure (28)(29)(30), and there are striking structural differences among variant influenza NA subtypes at this site (17,18,20). No 150-cavity in N10 could be identified compared with the uncomplexed typical group 1 VN04N1 (NA from Vietnam 2004 H5N1; PDB ID code 2HTY) and typical group 2 N2 structures (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…To consider the 150-loop width in Fig. 4(a), it can be seen that all quasispecies complexes, except for the C278Y variant, display a larger cavity compared with the WT, which suggests the transition of the 150-loop from closed to open form as evidenced in the previous study of Amaro et al (2011). These data support that mutations of the residues located at the back of the active site can affect the conformation of the 150-and 270-loops, such as driving the 150-loop from closed configuration into open form.…”
Section: Simulations Of the Quasispecies Populationsmentioning
confidence: 97%
“…As known, the 150-loop plays an important role for substrate and/or drug binding because this loop is flexible, revealing a closed and open cavity of the NA binding pocket (Amaro et al, 2007(Amaro et al, , 2009Han & Mu, 2013). The motion of this loop is coupled with the motion of the 430-loop; hence, the 150-cavity width was monitored as the distance between V149 and P431 residues (Amaro et al, 2011). In addition, the residues D151 and R152 belonging to the 150-loop can form hydrogen bonds with functional groups of NAIs (Le et al, 2010).…”
Section: Simulations Of the Quasispecies Populationsmentioning
confidence: 99%
“…The 150 loop was seen only in a closed configuration in the structure of N1 NA from the swine-origin virus A/California/04/2009 (H1N1) 31 . A molecular dynamics study suggested that the open form is preferred in solution and that the open form may also exist in avian N2 and earliest human N2 structures which lack a salt link from Asp 147 to Lys or His 150 that holds the loop closed in H5N1 NA 34 .…”
Section: Neuraminidase Structural Domainsmentioning
confidence: 99%